Disseminated tuberculosis with hydrocephalus and cerebral salt wasting syndrome: the importance of early diagnosis - Ana Raquel Mendes; Ana Lúcia Cardoso; Daniel Meireles; Alzira Sarmento; Alexandre Fernandes (Hygeia Press di Corridori Marinella, 2023)
Background: Tuberculosis (TB) remains an important global health problem. Children have greater risk than adults for developing severe disease manifestations, such as tuberculous meningitis (TM). Because TM usually presents with non-specific symptoms in the early stages of the disease, early diagnosis and management are important to prevent adverse outcomes.  Case presentation: A previously healthy 2-year-old boy without history of Bacillus Calmette-Guérin vaccination was admitted to a Pediatric Ward due to fever that persisted for 11 days and altered consciousness. On day 1 of admission, his consciousness worsened and he developed symptomatic seizures. Emergent head computed tomography revealed hydrocephalus. He was intubated and ventilated, and subsequently transferred to a Pediatric Intensive Care Unit, where an external ventricular drain was inserted. Head magnetic resonance imaging confirmed the presence of meningitis concentrated on the base of his brain, together with vasculitic phenomena and ischemic lesions. We decided to initiate oral quadruple anti-bacillary drug therapy and intravenous adjuvant corticosteroids. The culture and molecular analysis of the cerebrospinal fluid and respiratory secretions were positive for Mycobacterium tuberculosis complex. Because his hyponatremia persisted, despite increasing sodium supplementation and hypovolemia, we suspected cerebral salt wasting syndrome. He was therefore treated with oral fludrocortisone, which progressively improved his laboratory test results. The patient remained afebrile after day 4 and was extubated on day 10. He preferentially looked to his left, and other findings included right hemiparesis with increased muscular tone, right hand rhythmic finger movements, generalized hyperreflexia, bilateral hypertonia, and bilateral striatal hallux.  Conclusions: This case report emphasizes the importance of considering TB and TM in the differential diagnosis of a child with a fever of unknown origin to reduce the risk of short-term complications, such as seizures and hydrocephalus, and long-term complications, such as hemiplegia and cognitive impairment.